2017
DOI: 10.1002/jctb.5215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chloride and nitrate salts on Hg(II) sorption by raw and pyrolyzed malt spent rootlets

Abstract: BACKGROUND Mercury is considered to be one of the most harmful metals for human health and the environment. Biomass based materials and the corresponding biochars show promising potential as Hg(II) sorbents. Sorption is an effective process to remove Hg(II) from polluted waters, and is mainly affected by water chemistry. The sorption efficiency of malt spent rootlets and their biochar was evaluated at various ionic strength levels with two different salts, NaCl and NaNO3. RESULTS For both materials, the salts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…AC in "Hg + DOM" condition had the lowest q e (10.4 μg g − 1 ). In past studies, chloride interacting with Hg to form a stable complex was considered as the reason for decreasing the q e of adsorbent [41,42]. The additional sulfide seems to affect Hg adsorption on AC slightly.…”
Section: Preliminary Adsorption Capacity Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…AC in "Hg + DOM" condition had the lowest q e (10.4 μg g − 1 ). In past studies, chloride interacting with Hg to form a stable complex was considered as the reason for decreasing the q e of adsorbent [41,42]. The additional sulfide seems to affect Hg adsorption on AC slightly.…”
Section: Preliminary Adsorption Capacity Comparisonmentioning
confidence: 99%
“…Chen et al [43] reported that Hg 0 reemission rates from the wet flue gas desulfurization slurry increased about 4 μg m − 3 as the pH values increased from 3 to 7; the Hg 0 reemission rate decreased with increases chloride concentration. The acid condition could remain Hg + in the dissolved phase, as a result, Hg adsorption test was generally carried out under pH 3-5 [41,44,45]. However, the range of pH value is 6-8 in natural aquatic system.…”
Section: Preliminary Adsorption Capacity Comparisonmentioning
confidence: 99%
“…Their later study showed that the Hg sorption capacity by MSR biochars increased by a maximum factor of 6 for high-temperature (750-900℃) biochars compared to the raw material (Manariotis et al, 2015). Hg(II) sorption onto both materials carried on mainly through neutral species (Boutsika et al, 2017). Shi et al (2020) developed a ZnCl 2 -modified glue residue biochar for Cr(VI) sorption.…”
Section: Industrial Wastewatermentioning
confidence: 99%
“…Generally, biochar presents high surface area and a significant amount of surface groups (acidic or basic) that can participate in adsorption processes. The biochars can be used as fuels, immobilize heavy metals, pesticides and other organic pollutants, prevent bacteria and nitrates leaching in water, activate persulfates for the oxidation of pollutants, and act as catalysts or catalyst supports [17][18][19][20][21]. In the latter case, the composition of ash should be carefully examined because it may have catalytically active or poisoning species.…”
Section: Biocharmentioning
confidence: 99%